DEVELOPMENT OF HIGH SPEED PAINT MIXER - Norhayati, Ibrahim; Zulkhairi, Khairudin; Rohaiza, M Sahak Z (MATTER: International Journal of Science and Technology, 2020)
This study focuses on designing and developing a paint mixer that is suitable for small and medium industries. The paint mixer is designed to mix and blend the paint ingredient in an efficient way to improve the production rate as well as paint quality. The paint mixer equipped with a high shear blade powered by an electric motor can mix the paint ingredient up to 200 liter for 4 hours. Therefore, the productivity increases from 30 liter a day up to 400 liters in 8 hours. The paint ingredient is fully dissolved in a shorter time as compared to the manually mixing process. The mixing process also reduces energy consumption by mixing a large quantity of paint ingredients needed by the current method in the same quantity. Thus, this machine is able to help small and medium industries boost their production and profit.